TikTok Celebrities as Role Models: Imitation or Innovation? "Apakah Selebriti TikTok sebagai Panutan: Imitasi atau Inovasi?" - Haniyah Febriyanti Rosadi; Nur Maghfirah Aesthetika (Academia Open, 2024)
This qualitative study aimed to analyze the TikTok accounts of @ayuanzillah and @yusni.a, with a focus on the self-existence of teenagers in Jiken village. The study used purposive sampling and descriptive qualitative analysis to examine the videos uploaded on the accounts. The results showed that the videos were not original but rather copied from other sources, indicating a trend-following behavior rather than trend-setting. The TikTok celebrities exhibited a calm demeanor to maintain their online presence and avoid negative feedback from netizens. The motivational quotes shared on the platform were mostly based on personal experiences and aimed to inspire others. The study implies that TikTok celebrities can serve as role models for teenagers, but their influence should be monitored to ensure that they promote positive values and behaviors. Highlight: The study used purposive sampling and descriptive qualitative analysis to examine the TikTok accounts of @ayuanzillah and @yusni.a, with a focus on the self-existence of teenagers in Jiken village. The results showed that the videos were not original but rather copied from other sources, indicating a trend-following behavior rather than trend-setting. The study implies that TikTok celebrities can serve as role models for teenagers, but their influence should be monitored to ensure that they promote positive values and behaviors. TikTok has policies regarding inactive accounts and verified accounts. A verified badge means that TikTok has confirmed the account belongs to the person or brand it represents, and an inactive account may have its username reset if it remains inactive for 180 days or more Keywords: TikTok, Purposive sampling,Descriptive qualitative analysis,Trend-following behavior,Role models